Morphoanatomical plasticity of Tibouchina clavata (Melastomataceae) in ombrophilous forest and restinga forest - Melo Júnior, João Carlos Ferreira; Amorim, Maick William; Arriola, Igor Abba; Dirksen, Jessica Stefani; Andreacci, Fernando (Ciência e Natura, 2017)
Structural adjustments in plants may occur in response to environmental constraints, which may influence plant growth and development, as well as patterns of species coexistence. The present study aimed to evaluate the plastic responses of Tibouchina clavata (Melastomataceae) occurring in two forest formations governed by different environmental conditions. Ten leaves of ten individuals were collected in each formation, for a total of n = 100 per area. as were stem samples, for measuring architectural, morphological and foliar traits. Environmental variables considered included edaphic nutrition, water availability and light radiation. The phenotypic plasticity index was calculated for each trait. Morphoanatomical traits varied among populations with greater emphasis on plant height and stem diameter, in contrast to the lower variation observed for leaf traits. Foliar morphoanatomy met the expected pattern for plants that grow under conditions of greater luminosity. Greater development of the aerial system (height and diameter of the stem) was observed in the plants of the ombrophilous forest, indicating that this growth is related to the soil fertility and water availability. The phenotypic plasticity index indicates low plasticity for T. clavata in the geographic distribution studied.